Israi’liyat Materials in Tafsir al-Thabari - Nafisah Jali (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
Israi’liyat is a story that comes from Jews and Christians or interpretations that have no basis at all, either in the form of dhaif and maudu’ traditions, false ta’wil, or fantasies of contemporary commentators that are deliberately inserted into the interpretation. There are 38,397 narrations as a source of interpretation of Ma’tsur written by Ibn Jarir al-Thabari in his commentary, the history of Ma’tsur is based on the opinions and views of the companions and tabi’in. This research method uses a descriptive analysis method in which the author explains Israi’liyat in his commentary book Ibn Jarir al-Thabari and analyzes the sources of Israi’liyat interpretation contained in the book of al-Thabari’s interpretation. The results of this study are that after being analyzed, it turns out that the author found several narrations of Israi’liyat in a Thabari’s interpretation which was used as one of the sources of interpretation that Ibn Jarir al-Thabari used. The history of Israi’liyat is in accordance with Islamic teachings, some are not in accordance with Islamic teachings and Mauquf Israiliyat.